Nutrient recycling from organic wastes through viable business models in peri-urban areas in Sub-Saharan Africa - Danso, George K.; Drechsel, Pay (2014)
A major challenge of urbanisation, for relevant decision makers, is the provision of sufficient food and water for the emerging mega-cities and appropriate peri-urban sanitation management. This paper focuses on the results of a project carried out by International Water Management Institute (IWMI) in three major cities in Ghana. The project was designed to provide decision support for nutrient recycling from organic waste in peri-urban areas, through waste composting or co-composting with nightsoil. Experiences of existing compost stations from Nigeria, Benin, Mali, Burkina Faso and Togo were taken into consideration to formulate the research framework. Apart from the technical aspect, the study looked at actual waste supply and its quality, a quantification of the compost demand as well as economic viability of different scenarios and legal implications. The analysis showed that from the city perspective cost savings are only possible if large volumes of waste can be composted to reduce waste transport costs while compost sale (and agricultural use) is not a necessity from the perspective of cost savings. In fact, despite much interest the farmers’ willingness to pay remained limited at the reservation price of US$5 per 50 kg bag. As this includes transport costs peri-urban areas will be those benefiting most from composting projects. Closing the rural-urban nutrient cycle appears unrealistic given the increasing transport distance; at least as long as smallholder farmers are targeted. However, the consideration of alternative customer segments and implementation of innovative business models could help in reaching different scales.